Analysis of factors affecting the credit risk of Japanese commercial banks - Tang, Yutao (2019)
In modern society, commercial bank has become an indispensable financial intermediary in every country, which regulates the financial capital resources of the country.Undeniably, the banking boom or bust is also an indirect indicator of national economic strength.